ULTRASTRUCTURE OF THE Z LINE OF SKELETAL MUSCLE FIBERS - Rowe, R. W. (The Rockefeller University Press, 1971)
A new model of Z-line structure in skeletal muscle is proposed. Unlike previous models it is capable of explaining the two apparently inconsistent lattice arrangements seen in thin sections, i.e., the "basket weave" lattice and the smaller lattice recently reported in the literature. The model is based on four looping helical strands derived from the I filaments within the Z line. Each of these four strands form hairpin-shaped loops within the Z line and then join with an adjacent I filament in the same sarcomere. The two apparently different lattices represent a common structure viewed at slightly different levels of section.